Geruzz Courier's Social Contribution as an Online Courier, East Lombok District - Sekarsari, Nhan Cantik Anindhita; Rohmah, Ichmi Yani Arinda (LPPM Universitas Terbuka, 2023)
In the digital era, there is rapid growth in online shopping activities. Buyers can easily transact with merchants located in various locations around the world. Furthermore, the transacted goods will be sent via online courier service. In the process of distributing goods, online couriers function as a means of communication between sellers and buyers in doing something transaction ordered goods through online courier. Online couriers make it very easy for public in do booking items that will be ordered by the same consumer. This paper aims to examine the social capital and instrumental motivation of online couriers in East Lombok Regency. A type of literature study known as qualitative research was used in this research. According to the research findings, online couriers contribute to employment, create many job opportunities, alternative activity to fill free time, economic independenceand, encourage social change through conflict. Online couriers create new, fairer competition and influence existing social structures to create a fairer and more inclusive system. The increase in online couriers and public recognition of this application encourages social commitment to the presence of online delivery.